Production and incorporation of black soldier fly larvae frass in retaining nitrogen from urea - Visvini, Lohanathan; Latifah, Omar; Ahmed, Osumanu Haruna; Wei, Jie Kurk; Cassandra, David Sarah (Scholar Publishing, 2022)
Nitrogen (N) from urea application is not available in soils due to the fast release and loss through ammonia volatilization or nitrate leaching. Nitrogen could be retained in soil using organic amendment such as frass. The objectives of this study were to: (i) produce frass by rearing black soldier fly larvae (BSLF) with decanter cake (DC), (ii) determine the physico-chemical properties of frass produced from BSFL fed on DC, and (iii) determine urea-N retention in soil following BSFL frass application. The frass production was carried out by rearing BSFL using DC with the feeding rate of 200 mg larvae-1 day-1. The maturity of the BSFL frass was determined through physical, biological (phytotoxicity test), and chemical tests. A leaching study was carried out for 30 days by incorporating different rates of BSFL frass and urea. At 45 days of rearing, BSFL frass was produced whereby the insect larvae turn into pupae. The BSFL frass has good agronomic qualities which appropriate to be used as organic fertilizer. The BSFL frass were not toxic to white radish germination as reflected by the germination index ranged from 85% to 97%. Incorporation of BSFL frass with urea improved retention of N in the form of exchangeable NH4+ and available NO3- because of high TOC and TOM which related to the organic N decomposition into inorganic N. Combined application of BSFL frass and urea particularly reduced by half of recommended urea suggests that urea-N application can be properly improved if it is amended with BSFL frass.